PERBANDINGAN COBIT 2019 DAN ITIL V4 SEBAGAI PANDUAN TATA KELOLA DAN MANAGEMENT IT - Mohamad Adhisyanda Aditya; R Dicky Mulyana; Ali Mulyawan (Jurnal Computech & Bisnis (e-Journal), 2019)
Cobit 2019 and ITIL V4 are tools and guidelines that can be used to form an IT governance and management framework. There are several differences between the two, although they are also common and widely used for IT management and management implementation. Both are also the latest versions of the publications of the organizations that created them. With the help of Cobit 2019 or ITIL V4, organizations can be helped in implementing IT management and management. Not infrequently an organization feels confused in choosing tools or frameworks that will be used as the basis for implementing IT management and management. The literature study conducted aims to discuss the differences between the two as a guide to IT management and management. Keyword : ITIL, COBIT, IT Governance, IT ManagementDOI : http://doi.org/10.5281/zenodo.3631057